Fat metabolism during exercise: Mechanisms of regulation Metabolismo de gordura durante o exercício físico: Mecanismos de regulação - da Silva A.E.L.* (2006)
Fats are important energetic fuel to exercise. However, the regulation of fat uptake during exercise is unclear. The main objective of this review was to focus on physiological control mechanisms of mobilization, transport and fat uptake during exercise. The articles of fat metabolism were searched in Pubmed and Lilacs indexes. Classical and current papers were preferred. Evidence suggests that transport of fatty acids (FA) from extracellular to intracellular spaces could be the main factor to limit fatty acid uptake. Future studies on fat uptake during exercise can focus on this mechanism. In intense exercise, the lower blood flow in the adipose tissue and higher fatty acid reesterification rate impairs fat uptake during exercise. Supplementation of the FA has been used, however, the ideal quantities and forms to prevent gastrointestinal discomfort were not yet determined. In the biological point of view, intramuscular reserve of FA could be more efficient, because is not necessary to FA to cross the cell membrane.